2011
DOI: 10.1016/j.jcmg.2010.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Ischemia in the Absence of Obstructive Coronary Artery Disease in Systemic Lupus Erythematosus

Abstract: we observed a 44% prevalence of abnormal stress myocardial perfusion by CMR in the absence of obstructive CAD in SLE patients with anginal CP. Compared with controls, reduced MPRI was observed in SLE patients, and SLE presence was a significant predictor of an abnormal MPRI. These findings are consistent with the hypothesis that anginal CP in SLE patients without obstructive CAD is due to myocardial ischemia potentially caused by microvascular coronary dysfunction. Further research in a larger SLE population i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
108
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(110 citation statements)
references
References 29 publications
1
108
0
1
Order By: Relevance
“…Data are accumulating that microvascular dysfunction is an unrecognized source of anginal chest pain in patients with autoimmune diseases such as systemic lupus erythematosus (SLE) 1,2,3 . Studies show that microvascular impairment contributes to cardiovascular disease in other autoimmune conditions such as systemic sclerosis 1,2,4 .…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Data are accumulating that microvascular dysfunction is an unrecognized source of anginal chest pain in patients with autoimmune diseases such as systemic lupus erythematosus (SLE) 1,2,3 . Studies show that microvascular impairment contributes to cardiovascular disease in other autoimmune conditions such as systemic sclerosis 1,2,4 .…”
Section: To the Editormentioning
confidence: 99%
“…Studies show that microvascular impairment contributes to cardiovascular disease in other autoimmune conditions such as systemic sclerosis 1,2,4 . Patients with SLE presenting with anginal chest pain pose a diagnostic challenge.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies from our institution have shown that by using cardiac magnetic resonance (CMR), a prevalence of abnormal stress myocardial perfusion in SLE patients with anginal chest pain in the absence of obstructive coronary artery disease can be observed [7]. SLE patients are particularly at risk of overuse of the emergency department [8].…”
Section: Discussionmentioning
confidence: 99%
“…CMR has been used to detect myocardial scars in those patients [79]. Recent work by Ishimori et al even revealed abnormal myocardial CMR stress perfusion despite normal coronary angiography, indicating microvascular impairment [80]. Increased myocardial T2-times were able to differentiate Lupus patients in active inflammation from those in inactive phases or controls [81].…”
Section: Lupusmentioning
confidence: 99%